2007
DOI: 10.1158/1078-0432.ccr-07-1230
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sentinel Lymph Node Lymphangiogenesis is Associated with Nonsentinel Axillary Lymph Node Involvement in Breast Cancer Patients with a Positive Sentinel Node

Abstract: Purpose: Lymph node (LN) lymphangiogenesis has recently been shown to be important in the premetastatic niche of sentinel LNs. To study its role in the further metastatic spread of human breast cancer, we investigated the association of angiogenesis and lymphangiogenesis in sentinel LN metastases with the presence of nonsentinel LN metastases in breast cancer patients with a positive sentinel LN. Experimental Design: Angiogenesis and lymphangiogenesisöquantified as endothelial cell proliferation fraction (ECP%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…Active lymphangiogenesis was also detected in positive sentinel LN (22,23) that displayed a signifi cantly higher median LECP% (p < 0.001) than uninvolved LN (23). Moreover, high frequency of Ki-67-labeled lymphatics in positive sLN was strongly associated (p = 0.01) with axillary metastasis (22), supporting the contention that tumor-induced lymphangiogenesis promotes dissemination from both the primary tumor and secondary metastatic sites. Nevertheless, with the exception of very active lymphangiogenesis in infl ammatory breast cancer (20,21), a relatively low fraction of dividing lymphatic endothelial cells (2-6%) and some discrepancy between high %LVI and low %LECP in other breast cancer types suggest that both new and existing lymphatic vessels partake in lymphatic metastasis (24).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Active lymphangiogenesis was also detected in positive sentinel LN (22,23) that displayed a signifi cantly higher median LECP% (p < 0.001) than uninvolved LN (23). Moreover, high frequency of Ki-67-labeled lymphatics in positive sLN was strongly associated (p = 0.01) with axillary metastasis (22), supporting the contention that tumor-induced lymphangiogenesis promotes dissemination from both the primary tumor and secondary metastatic sites. Nevertheless, with the exception of very active lymphangiogenesis in infl ammatory breast cancer (20,21), a relatively low fraction of dividing lymphatic endothelial cells (2-6%) and some discrepancy between high %LVI and low %LECP in other breast cancer types suggest that both new and existing lymphatic vessels partake in lymphatic metastasis (24).…”
Section: Discussionmentioning
confidence: 64%
“…Studies that compared LECP% in infl ammatory and noninfl ammatory breast cancers found that the former have both a higher incidence of Ki-67 positive lymphatics (80% vs. 50%) and an increased median LECP% (20,21). Active lymphangiogenesis was also detected in positive sentinel LN (22,23) that displayed a signifi cantly higher median LECP% (p < 0.001) than uninvolved LN (23). Moreover, high frequency of Ki-67-labeled lymphatics in positive sLN was strongly associated (p = 0.01) with axillary metastasis (22), supporting the contention that tumor-induced lymphangiogenesis promotes dissemination from both the primary tumor and secondary metastatic sites.…”
Section: Discussionmentioning
confidence: 98%
“…Another contributing factor for lymphatic metastasis is the increased lymphangiogenesis in sentinel lymph nodes draining a tumor (Hirakawa et al 2005;Van den Eynden et al 2007;Rinderknecht and Detmar 2008;Ruddell et al 2008). Besides the lymphangiogenic factors transported with lymph from tumor, lymphocytes in lymph nodes also actively participate in the regulation of lymph nodeassociated lymphatic vessel growth.…”
Section: Interaction Of Tumor Cells and Lecs During Tumor Invasionmentioning
confidence: 99%
“…Lymph node lymphangiogenesis has also been shown to be associated with lymphatic metastases in animal models (16,17). It has been shown that the lymphangiogenesis in the sentinel lymph node is initiated before tumor metastasis in the lymph nodes (18,19). Thus, lymph node lymphangiogenesis can be an important factor in lymph node tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-C is an angiogenic factor mainly involved in lymphatic endothelial cell (LEC) growth. Macrophages produce and secrete VEGF-C and play a critical role in lymphangiogenesis (19). VEGF-C from macrophages induces lymphangiogenesis in advanced ovarian cancer (20).…”
Section: Introductionmentioning
confidence: 99%